Catalyst supporting method for methanol-steam reforming hydrogen-producing system - ZHANG YUFENG; ZHANG XUELIN; TUO YANJING; LIU XIAOWEI (2015)
The invention relates to a catalyst supporting method for a methanol-steam hydrogen-producing system, and concretely relates to a catalyst supporting method for improving performances of a methanol-steam minisize reformer. In order to solve the problems that reformer performances decreases because of falling off of a catalyst, the fell catalyst blocks air outlets, and the like, surface electrochemical corrosion is performed on a micro-channel aluminium plate, so that formed stepwise pores help to increase the surface roughness and the specific surface area. Then the aluminium plate subjected to electrochemical etching is oxidized in diluted nitric acid, so that a thin oxidation layer is formed on the surface and is used to provide a support for the catalyst and enable the catalyst to relatively easily attach to the carrier. Due to the fact that the catalyst is supported on the surface of the micro-channel aluminium plate processed according to the above process, the catalyst adhesion amount is increased, the adhesiveness of the catalyst on the carrier is improved, and thus the methanol conversion rate is improved and the performances of the methanol-vapor minisize reformer are improved.